Enrichment and Correlation Analysis of Serum miRNAs in Comorbidity Between Arnold-Chiari and Tourette Syndrome Contribute to Clarify Their Molecular Bases - Mirabella, Federica; Gulisano, Mariangela; Capelli, Mara; Lauretta, Giovanni; Cirnigliaro, Matilde; Palmucci, Stefano; Stella, Michele; Barbagallo, Davide; Di Pietro, Cinzia; Purrello, Michele; Ragusa, Marco; Rizzo, Renata (Frontiers in Molecular Neuroscience, 2021)
Due to its rarity, coupled to a multifactorial and very heterogeneous nature, the molecular etiology of Arnold-Chiari (AC) syndrome remains almost totally unknown. Its relationship with other neuropsychiatric disorders such as Tourette syndrome (TS) is also undetermined. The rare comorbid status between both disorders (ACTS) complicates the framework of diagnosis and negatively affects the patients’ quality of life. In this exploratory study, we aimed to identify serum microRNA expression profiles as molecular fingerprints for AC, TS and ACTS, by using a high-throughput approach. For this aim, 10 AC patients, 11 ACTS patients, 6 TS patients, and 8 unaffected controls (NC) were recruited. Nine miRNAs resulted significantly differentially expressed (DE): let-7b-5p (upregulated in ACTS vs TS); miR-21-5p (upregulated in ACTS vs AC; downregulated in AC vs TS); miR-23a-3p (upregulated in TS vs NCs; downregulated in AC vs TS); miR-25-3p (upregulated in AC vs TS and NCs; downregulated in ACTS vs AC); miR-93-5p (upregulated in AC vs TS); miR-130a-3p (downregulated in ACTS and TS vs NCs); miR-144-3p (downregulated in ACTS vs AC; upregulated in AC vs TS); miR-222-3p (upregulated in ACTS vs NCs); miR-451a (upregulated in AC vs TS and NCs; in ACTS vs NCs). Altered expression of miRNAs was statistically correlated to neuroimaging and neuropsychological anomalies. Furthermore, computational analyses indicated that DE miRNAs are involved in AC and TS pathomechanisms. Finally, we propose the dysregulation of the miRNA set as a potential molecular tool for supporting the current diagnosis of AC, TS and ACTS by using liquid biopsies, in an unbiased and non-invasive way.